2013
DOI: 10.1111/jrh.12032
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Avoidance Among Rural Populations: Results From a Nationally Representative Survey

Abstract: Background Previous research suggests that certain populations, including rural residents, exhibit health care avoidant behaviors more frequently than other groups. Additionally, health care avoidance is related to sociodemographics, attitudes, social expectations, ability to pay for care, and prior experiences with providers. However, previous studies have been limited to specific geographic areas, particular health conditions, or by analytic methods. Methods The 2008 Health Information Trends Survey (HINTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
94
3
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 26 publications
13
94
3
5
Order By: Relevance
“…This study found fewer mean ER visits in the past 12 months than the most recent national data, but a greater proportion using the ER at least once. Once again, these results support previous research that has reported rural residence as a risk factor for avoidance of health services (Spleen et al, 2014).…”
Section: Racesupporting
confidence: 81%
See 4 more Smart Citations
“…This study found fewer mean ER visits in the past 12 months than the most recent national data, but a greater proportion using the ER at least once. Once again, these results support previous research that has reported rural residence as a risk factor for avoidance of health services (Spleen et al, 2014).…”
Section: Racesupporting
confidence: 81%
“…These results in combination with previous results (Rew, et al, 2007), suggest that healthy lifestyle behaviors may be lowest at approximately ages 17-19. Steinberg posits that high-risk reward-seeking behavior associated with normal cognitive development peaks around age 15 and declines with further cognitive development that improves adolescents' self-regulation abilities (Steinberg, 2010 (Spleen et al, 2014) and the sample in this study was consistent with this pattern. It seems unlikely that adolescents living in a rural area would have less need for HCP visit than urban adolescents-especially considering the high rates of HCP diagnosed conditions reported by this sample.…”
Section: Racesupporting
confidence: 74%
See 3 more Smart Citations